Development of Test Instruments in Substance Pressure to Measure Student's Numerical Literacy Ability - Fatmala, Rita Iva; Rusilowati, Ani; Astuti, Budi (Universitas Negeri Semarang, 2023)
The purpose of this study was to develop an instrument test to measure student's numeracy literacy skills on substance pressure and its application. The research was conducted using the Research and Development (RD) development method trough the ADDIE research design (Analysis, Design, Development, Implementation, and Evaluation) through several stages, namely curriculum analysis, content analysis, context analysis, and determining instrument framework, instrument development, pilot testing instrument and item analysis of the instrument. The trial was conducted on a sample determined by a random sampling technique. The item analysis of the instrument includes item validity test, item reliability test, item difficulty level, and item discriminatory power. The results of this study were the test instrument of numeracy literacy in the form of multiple-choice questions with 18 reliable questions with a reliability coefficient of 0.903. Based on the validity test, there are 5 questions with moderate validity category, 10 questions with high validity category, and 3 questions with very high validity category. Based on the results of the discriminatory power test and the level of difficulty of the questions, it was obtained that all questions had distinguishing power in the good category with the difficulty level of the questions in the easy, medium, and difficult category are 1, 13, and 4 questions, respectively. Therefore, it can be concluded that the numerical literacy test instrument on the substance pressure material and its application can be used as a test instrument to measure student's numeracy literacy skills.